Stress, self-compassion, and well-being during the transition to college. (January 2021) - Kroshus, Emily; Hawrilenko, Matt; Browning, Anne
Abstract: Rationale: The transition to college presents a period of vulnerability to mental illness, and opportunity for positive psychosocial development. Objective: The present study sought to build an explanatory person-centered and contextualized model of student wellbeing in the transition to college. Method: Participants were entering first year undergraduate students at a large public university in the United States (n = 5509). Online survey data were collected at three time points across the academic year, with outcomes of depression and anxiety, thriving, and grade point average, and predictors including resilient coping, self-compassion, social support, school connections and the acute and chronic stressors experienced during the transition to college. Latent growth curves were used to examine trajectories of change in depression and anxiety, and a cross-lagged panel model was used to describe a system of how all measured variables influenced each other over time. Results: There were four main findings. On average, students experienced moderate increases in depression and anxiety from the summer before college through the spring, with wide variability across students and no clear patterning by demographic groups. Second, self-compassion was the strongest and most consistent predictor of successful transitions. Third, chronic stressors were strongly predictive of more negative outcomes, and self-compassion and coping skills did not buffer their effects. Finally, people most likely to experience chronic stressors over the school year included women, people who identify as sexual minorities and first-generation students. Conclusions: Programming to support entering college students should seek to foster self-compassion, while also limiting chronic stressors and reducing their inequitable distribution across the student population. Highlights: Self-compassion predicted better mental health across the first year of college. Chronic stressors predicted worse mental health and academic outcomes. Female, sexual minority and first-generation students faced the most chronic stress. Self-compassion did not buffer the negative effects of chronic stressors.